Family Empowerment to Improve Dietary Adherence Among Pregnant Women with Gestational Diabetes in the Sumbersari Community Health Center Service Area, Jember (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Gestational diabetes mellitus (GDM) is a growing global maternal health concern that increases the risk of adverse outcomes for both mothers and infants. In Indonesia, the prevalence of GDM continues to rise due to changes in lifestyle, dietary habits, and metabolic risk factors among pregnant women. Dietary management remains the cornerstone of GDM treatment; however, maintaining adherence to dietary recommendations is often challenging because pregnant women must consistently modify long-established eating behaviors. Family involvement is increasingly recognized as an important factor that may enhance adherence to therapeutic diets during pregnancy. This study aimed to analyze the relationship between family empowerment and dietary adherence among pregnant women with GDM in the Sumbersari Community Health Center service area, Jember. A quantitative study with an observational analytic and cross-sectional design was conducted involving 45 third-trimester pregnant women diagnosed with GDM. All eligible participants were included using a saturated sampling technique. Data were collected through validated questionnaires measuring family empowerment and dietary adherence and were analyzed using the Chi-square test. The results revealed a significant relationship between family empowerment and dietary adherence (p = 0.000; p < 0.05). Pregnant women who received greater family empowerment demonstrated higher levels of dietary adherence. Strengthening family-centered interventions may improve dietary compliance and support better glycemic control among women with GDM.